2009
DOI: 10.1007/s12094-009-0383-1
|View full text |Cite
|
Sign up to set email alerts
|

Spanish Society of Medical Oncology consensus for the use of haematopoietic colony-stimulating factors in cancer patients

Abstract: Neutropenia is a common complication of cancer chemotherapy. Colony-stimulating factors (CSF) may be used to avoid neutropenia-associated complications. The Spanish Society of Medical Oncology (SEOM) recently constituted a working group to review the main issues concerning the use of CSF and carried out a consensus process about the use of CSF in cancer patients, held in Madrid on 26 May 2006. The group concluded the following recommendations: prophylactic use of CSF is recommended when a rate of febrile neutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Official guidelines from Europe and the USA now agree that primary G-CSF prophylaxis should be given when the overall risk of FN due to regimen and patient factors is ≥20% [1620]. Prior to 2006, primary G-CSF prophylaxis was recommended for chemotherapy regimens associated with a relatively high FN risk of 40% [21].…”
Section: Who Should Receive G-csfs?mentioning
confidence: 99%
“…Official guidelines from Europe and the USA now agree that primary G-CSF prophylaxis should be given when the overall risk of FN due to regimen and patient factors is ≥20% [1620]. Prior to 2006, primary G-CSF prophylaxis was recommended for chemotherapy regimens associated with a relatively high FN risk of 40% [21].…”
Section: Who Should Receive G-csfs?mentioning
confidence: 99%
“…In fact, the Spanish Society of Medical Oncology, in accordance with European and US guidelines, recommends G-CSF use in patients with a risk of FN of >20% (17)(18)(19). A multicenter trial involving 210 patients from five Spanish hospitals revealed that the duration of hospitalization was significantly shorter in the group of patients receiving G-CSF (5 days), compared with that in the control group (7 days) (14).…”
Section: Discussionmentioning
confidence: 99%
“…Prophylactic treatment with granulocyte colony-stimulating factor (G-CSF) was found to be beneficial regarding patient survival and a reduction in the risk of FN (14)(15)(16). Since it is common to develop FN during the first cycle of chemotherapy, European and US guidelines recommend the use of G-CSF in patients with an FN risk of >20% (17)(18)(19). Despite widespread research into chemotherapy usage, the risk of chemotherapy-induced FN in clinical practice is poorly documented.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] G-CSF is also recommended to support dosedense and dose-intense chemotherapy and to help maintain dose intensity where reductions and delays have been shown to adversely affect outcomes. [6] In breast cancer, regimens containing an anthracycline and a taxane have become standard of care in the adjuvant setting due to their high efficacy.…”
Section: Introductionmentioning
confidence: 99%